2006
DOI: 10.1182/blood-2006-01-023127
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tumor-associated antigens in acute myeloid leukemia: implications for specific immunotherapeutic approaches

Abstract: The expression of tumor-associated antigens (TAAs) might play a critical role in the control of minimal residual disease (MRD) in acute myeloid leukemia (AML), and therefore might be associated with clinical outcome in AML. In a DNA microarray analysis of 116 AML samples, we found a significant correlation between high mRNA levels of G250/CA9 and longer overall survival (P ‫؍‬ .022), a similar trend with high mRNA levels of PRAME (P ‫؍‬ .103), and a hint for RHAMM/HMMR. In contrast, for other TAAs like WT1, TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
174
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(192 citation statements)
references
References 41 publications
14
174
2
2
Order By: Relevance
“…Patients with the BCR/ABL t(9;22) (Ph+) and AML1/ETO t(8;21) translocations show particularly high PRAME mRNA levels (8,15,16). It cannot be excluded, however, that the correlation of PRAME expression with good prognosis is secondary to its correlation with these translocations (17). Indeed, it has been shown that PRAME is a BCR/ABL-inducible gene (15).…”
Section: Expression Of Preferentially Expressed Antigen Of Melanoma Imentioning
confidence: 94%
“…Patients with the BCR/ABL t(9;22) (Ph+) and AML1/ETO t(8;21) translocations show particularly high PRAME mRNA levels (8,15,16). It cannot be excluded, however, that the correlation of PRAME expression with good prognosis is secondary to its correlation with these translocations (17). Indeed, it has been shown that PRAME is a BCR/ABL-inducible gene (15).…”
Section: Expression Of Preferentially Expressed Antigen Of Melanoma Imentioning
confidence: 94%
“…88 A similar observation was made regarding PRAME, which is known to contain at least four different HLA-A*0201-restricted epitopes that can be naturally recognized (PRA [100][101][102][103][104][105][106][107][108] , PRA 142-151 , PRA 300-309 and PRA [425][426][427][428][429][430][431][432][433] ). 64 According to Greiner et al, 25 up to 70% of AML patients in complete remission spontaneously exhibit circulating PRA 300-309 -specific CTLs, further underscoring the significant natural immunogenicity of PRAME. 25 CD8 þ T cells specific for G250/CAIX [24][25][26][27][28][29][30][31][32] , G250/CAIX 254-262 and RHAMM [165][166][167][168][169][170][171][172][173] are also regularly detected in the peripheral blood of AML patients, with frequencies of 60%, 13% and 47%, respectively.…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 99%
“…Majeti et al 29 compared the gene expression signature of LSCs with that of normal HSCs and identified over 3000 genes with dysregulated expression in LSCs. 29 The published data set also includes several genes encoding proteins that can be recognized by the immune system and act as LAAs, such as Elicited (T) 47,95 Natural (B/T) 25 …”
Section: Criterion 2: Frequency and Pattern Of Expressionmentioning
confidence: 99%
See 2 more Smart Citations